A4 5 Jellyfish Jam - Savic, Natasha; Birch, Hannah; Tzabach, Lee (Physics Special Topics, 2023)
In this paper, we investigate how many jellyfish are required to power Karen's laser from the show SpongeBob SquarePants for an hour. We calculate the energy released from an average jellyfish sting as well as the energy required to power a 5 W laser for an hour. Assuming each jellyfish produces one sting, we require 258 jellyfish to power this laser.